Bridging Rigidity and Flexibility: Modulation of Supramolecular Hydrogels by Metal Complexation. Issue 12 (17th September 2021) - Stach, Oliver S.; Breul, Katharina; Berač, Christian M.; Urschbach, Moritz; Seiffert, Sebastian; Besenius, Pol
Abstract: The combination of complementary, noncovalent interactions is a key principle for the design of multistimuli responsive hydrogels. In this work, an amphiphilic peptide, supramacromolecular hydrogelator which combines metal‐ligand coordination induced gelation and thermoresponsive toughening is reported. Following a modular approach, the incorporation of the triphenylalanine sequence FFF into a structural ( C 3 EG ) and a terpyridine‐functionalized ( C 3 Tpy ) C 3 ‐symmetric monomer enables their statistical copolymerization into self‐assembled, 1D nanorods in water, as investigated by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). In the presence of a terpyridine functionalized telechelic polyethylene glycol (PEG) cross‐linker, complex formation upon addition of different transition metal ions (Fe 2+, Zn 2+, Ni 2+ ) induces the formation of soft, reversible hydrogels at a solid weight content of 1 wt% as observed by linear shear rheology. The viscoelastic behavior of Fe 2+ and Zn 2+ cross‐linked hydrogels are basically identical, while the most kinetically inert Ni 2+ coordinative bond leads to significantly weaker hydrogels, suggesting that the most dynamic rather than the most thermodynamically stable interaction supports the formation of robust and responsive hydrogel materials. Abstract : Supramolecular peptide nanorods are produced and interconnected through metallo‐supramolecular bis ‐terpyridine complexes in the presence of transition metals (Zn 2+, Fe 2+ and Ni 2+ ) and a telechelic polyethylene glycol cross‐linker at a concentration of 1 wt% in water. The viscoelastic behavior of the reversibly cross‐linked hydrogels is modulated via the transition metal, while thermal toughening is applied using thermoresponsive oligoethylene glycol chains.